Pengaruh Demografi dan Kebijakan Pemerintah Jepang Terhadap Depopulasi Negara Jepang Selama 2 Dekade Terakhir - Muhammad Praja Wibawa; Rani Arfianty (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2024)
Depopulation is an event of a continuous decline in population over time in an area. This research starts from the discovery of problems in the phenomenon of depopulation in Japan, among the causes are demographic factors and Japanese government policies. Because of this, research was conducted with the aim of finding the causes of depopulation of Japan from the analysis of demographics and Japanese government policies in the past 2 decades. The method used is data collection by finding data sources and comparing data from various sources such as news media, statistics, and existing research. The results show how demographic changes occur and government policies towards these changes. To determine its impact on the current depopulation phenomenon in Japan. Through research on demographic change and Japanese government policy, it can be concluded that demographic change does not always have a negative impact but can also have a positive impact both in terms of population parameters and other aspects.